A Chinese Herbal Preparation, Xiao-Er-An-Shen Decoction, Exerts Neuron Protection by Modulation of Differentiation and Antioxidant Activity in Cultured PC12 Cells. (3rd May 2018) - Li, Zhonggui; Lam, Kelly Y. C.; Liu, Xiaoyan; Qi, Airong; Yao, Ping; Dong, Tina T. X.; Yi, Tiegang; Tsim, Karl W. K.; Chen, Jianping
Abstract : Xiao-Er-An-Shen Decoction (XEASD), a Chinese herbal formula, has been used in clinic for treating insomnia and mental excitement in children and adolescents. However, less of scientific data supports its effectiveness in clinic. Here, we aim to study the role of XEASD in regulating neuron differentiation and antioxidant activity. An HPLC-MS was used to chemically standardize herbal extract of XEASD. The standardized herbal extracts of XEASD (0.3–3.0 mg/mL) were applied onto cultured PC12 cells for 48 hours. The treatment with XEASD extract induced neurite outgrowth of PC12 cells in a dose-dependent manner, having the highest response by 50% of differentiated cells. Application of XEASD extract dose dependently stimulated expressions of NF68, NF160, and NF200 in cultured PC12 cells. Furthermore, XEASD activated the phosphorylation of cAMP responsive element binding protein on PC12 cells, the effect of which was blocked by H89, a protein kinase A inhibitor. Moreover, XEASD showed free radical scavenging activity and stimulated the transcriptional activity of ARE. These results supported the neurobeneficial effects of XEASD in the induction of neurite outgrowth and protection against oxidative stress and could be useful for neurological diseases, in which neurotrophin deficiency and oxidation insult are involved.